Identifikasi Massa Air Di Perairan Timur Laut Samudera Hindia - M. Albab Al Ayubi; Heron Surbakti; La Ode Nurman Mbay (UNIVERSITAS SRIWIJAYA, 2013)
The northeast Indian Ocean is a region crossed by the monsoon winds and bordered by mainland on northern and eastern side that allegedly the water mass is influenced by these two factors. This research aims to study the vertical dan cross section distribution of physical parameters such as temperature, salinity, and density and also to identify the types of water masses in the region. The data used are the data of temperature, salinity, and density during 2007-2010 is obtained from sensors located on spacecraft of ATLAS Mooring. There are six stations located on the 90oE and from 0-15 oN, with 4 year observation and there are 4 periods each year.Â The results of observations of temperature on the surface indicates the period from December to February and March to May have a similar pattern. While the pattern in the period from June to August is similar to September-November. In other hand, the temperatures around depth of 140 m to the bottom shows the same pattern throughout the year. Value of the sea surface temperature of the period from March to May is generally the highest. Observations of sea surface salinity and water column generally are the same in each period, the salinity values decreased from a low-latitude station towards the high-latitude stations. The differences found are the highest surface salinity values are more common in the period from December to February, which is found on the station I and III. The result of value sea surface density observations show a decline pattern of low-latitudes stations in to higher latitudes stations throughout the year, or a pattern that tends to the same of salinity pattern.Â Analysis of the TS diagram refer to Wyrtki (1961) and Emery (2003) indicates there are some type of water masses, ther are namely the Bengal Bay Water (BBW), South Indian Central Water (SICW), Indian Equatorial Water (IEW), Subtropical Lower Water (SLW), and Northern Salinity Minimum (NSM). Those water masses is found in every period, only period from December to February have differrent type of water masses, that is the Arabian Sea Water (ASW).Keywords: ATLAS Mooring, Diagram TS, Indian Ocean, Water Mass